Giant Negative Electrocaloric Effect in Antiferroelectric La‐Doped Pb(ZrTi)O3 Thin Films Near Room Temperature. (11th April 2015) - Geng, Wenping; Liu, Yang; Meng, Xiangjian; Bellaiche, Laurent; Scott, James F.; Dkhil, Brahim; Jiang, Anquan
<x xml:space="preserve">Abstract</x> Antiferroelectric thin films are demonstrated as a new class of giant electrocaloric materials that exhibit a negative electrocaloric response of about −5 K near room temperature. The giant negative electrocaloric effect may open up a new paradigm for light, compact, reliable, and high‐efficiency refrigeration devices.